Determinant Behavioral Factors in Adolescent Anemia: Logistic Regression Analysis - Herawati, Cucu; Rahma Muthia, Widya; Dharmawan, Akim; Hendriyanto, Hendriyanto; Yulistiyana, Laili Nurjannah (Green Publisher Indonesia, 2025)
The incidence of anemia in the study location is the highest in Central Java, based on anemia screening among adolescent girls. Anemia during adolescence can negatively affect growth and development, brain function, learning capacity, and future reproductive health. Several factors may influence the occurrence of anemia in adolescents, including knowledge, habits, dietary practices, tea consumption, parental support, and participation in the school-based iron supplementation program TTD. This study aimed to analyze the role of behavioral determinants in the incidence of anemia among adolescents. This study employed a quantitative cross-sectional design. The population consisted of female tenth-grade students from public senior high schools and vocational high schools in East Tegal District, Tegal City, totaling 913 students. A sample of 90 respondents was selected using proportional random sampling. Data were collected through interviews and hemoglobin measurements. Data analysis was conducted using the Chi-square test and multivariate binary logistic regression. The results showed that tea consumption habits (p = 0.015), parental support (p = 0.002), and participation in the TTD consumption movement at school (p = 0.008) were significantly associated with the incidence of anemia in adolescents. Meanwhile, knowledge (p = 0.098) and consumption of iron-containing foods (p = 0.377) were not significantly associated with anemia. Parental support was identified as the most dominant factor, with a p-value of 0.005 and an odds ratio (OR) of 6.0. Collaboration between schools and community health centers is expected to strengthen parental education and anemia prevention efforts among adolescent girls.